Respuesta :

Answer: t = 6/11

Step-by-step explanation:

3t - 2 + t = 4 - 7t

4t - 2 = 4 - 7t

4t + 7t = 4 + 2

11t = 4 + 2

11t = 6

Divide both by 11

Answer : t = 6/11

Answer:

t = 6/11

Step-by-step explanation:

Hello!

Solve the equation for t by isolating the variable.

Solve for t

  • 3t - 2 + t = 4 - 7t        Add like Terms
  • 4t - 2 = 4 - 7t             Collect Like terms
  • 11t - 2 = 4                   Isolate the Variable
  • 11t = 6                        Isolate the Variable
  • t = 6/11

The value for t is 6/11.